MOSQUE-BASED ISLAMIC FINANCIAL INNOVATION TO IMPROVE THE WELFARE OF VILLAGE COMMUNITIES - Akmal Khairi; Fadli Daud Abdullah; Anas Bayan Mubarok (Gunung Djati Conference Series, 2025)
This study aims to examine the role of mosque-based Islamic financial innovation in improving the welfare of rural communities. The method used in this study is qualitative with a literature study approach. Data sources were obtained from various literature such as books, scientific journals, articles, and official documents relevant to the research theme. Data analysis techniques were carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that mosques have strategic potential as community-based economic centers because of their social and emotional closeness to rural communities. Through the management of zakat, infaq, sedekah, and waqf (ZISWAF) funds, as well as the implementation of sharia contracts such as qardhul hasan, murabahah, and musyarakah, mosques can become inclusive and usury-free Islamic microfinance institutions. This innovation is able to provide access to financing for small business actors, farmers, housewives, and poor rural communities, thereby encouraging local economic growth. In addition, the presence of mosques as financial centers also strengthens social solidarity, increases sharia financial literacy, and expands community participation in productive activities. By strengthening management, utilizing technology, as well as regulatory support and collaboration with Islamic financial institutions, mosques can become agents of significant socio-economic transformation in realizing sustainable and equitable village welfare.